Annual Hospital Volume of High Dose Interleukin-2 and Inpatient Mortality in Melanoma and Renal Cell Carcinoma Patients. - Kathan Mehta; Leonard Appleman; Hong Wang; Ahmad A Tarhini; Rahul A Parikh (PLoS ONE, 2016)
BACKGROUND:Immunotherapy using high dose interleukin-2 (HD IL2) in patients with renal cell carcinoma (RCC) and melanoma is associated with severe toxicities. The association between annual hospital volume of HD IL2 and inpatient mortality is not well studied. In this study we aim to quantify the impact of annual hospital volume of HD IL2 on inpatient mortality using National Inpatient Sample (NIS) data. METHODS:We did a cross-sectional study using NIS, one of the largest inpatient datasets in United States, from 2003 to 2011. Patients with melanoma and RCC receiving HD IL2 were identified by ICD9 procedure code 00.15. The primary outcome was inpatient mortality. Using Joinpoint regression, which detects change in trend of inpatient mortality with change in annual volume, the hospitals were classified in three volume categories (low: 1-40, medium: 41-120, high: >120). Multivariate logistic regression was used to identify predictors of inpatient mortality controlling for confounders. RESULTS:From 2003 to 2011, 29,532 patients with RCC or melanoma who received HD IL2 were identified, and 124 died during the hospitalization (0.4%). The hospitals with low, medium and high annual volume had significant difference in inpatient mortality (0.83%, 0.29% and 0.13% respectively, p = 0.0003). On multivariate analysis, low volume hospitals were associated with significantly higher odds of inpatient mortality (OR 6.1, 95% CI 1.6-23.2, p = 0.003) as compared to high volume hospitals. Additionally, the hospitals with annual volume of 1-20 had even higher rates (1.31% vs. 0.13%, p<0.0001) and multivariate odds (OR 8.9, 95% CI 2.4-33.2, p = 0.0006) of inpatient mortality as compared to high volume hospitals. CONCLUSIONS:Lower annual hospital volume of HD IL2 is associated with worse outcomes. Annual hospital volume of 1-40 and 1-20 treatments per year is associated with 6 and 9 times higher odds of inpatient mortality respectively as compared to high volume hospitals. Our findings provide preliminary evidence for a volume-outcome relationship for RCC and melanoma patients undergoing HD IL2 treatment. They support future volume-outcome analyses in relation to other anti-cancer therapies that require special training and expertise.